2015
DOI: 10.1080/02678373.2015.1031856
|View full text |Cite
|
Sign up to set email alerts
|

Mastery-approach and mastery-avoidance goals and their relation with exhaustion and engagement at work: The roles of emotional and instrumental support

Abstract: The results of two cross-sectional studies (N = 220 and N = 258) indicate that employees' workrelated mastery-approach goals (i.e. the striving to improve one's performance at work) were positively associated with work engagement. Further, this relationship is explained by high levels of instrumental support. In contrast, employees' work-related mastery-avoidance goals (i.e. the striving to avoid performing worse than one aspires to) are positive predictors of job detachment and fatigue. The relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 60 publications
8
23
2
1
Order By: Relevance
“…We extend the findings of achievement goal theory (Darnon, Butera, et al ., ; Darnon, Doll, et al ., ; Darnon et al ., ; Poortvliet & Giebels, ; Poortvliet et al ., , , ; Sommet et al ., ) by adding a focus on how avoid orientation impacts passive‐aggressive and dysfunctional behaviour patterns, and the potential detrimental impact an avoid orientation can have on managers. Our study is consistent with recent findings reporting that mastery approach and mastery avoidance goals are related to job engagement and fatigue through instrumental exchange relationships and emotional support (Poortvliet, Anseel, & Theuwis, ). This reinforces the need for additional research examining the relationships between GO, interpersonal exchanges, and managers’ emotional exhaustion.…”
Section: Discussionsupporting
confidence: 93%
“…We extend the findings of achievement goal theory (Darnon, Butera, et al ., ; Darnon, Doll, et al ., ; Darnon et al ., ; Poortvliet & Giebels, ; Poortvliet et al ., , , ; Sommet et al ., ) by adding a focus on how avoid orientation impacts passive‐aggressive and dysfunctional behaviour patterns, and the potential detrimental impact an avoid orientation can have on managers. Our study is consistent with recent findings reporting that mastery approach and mastery avoidance goals are related to job engagement and fatigue through instrumental exchange relationships and emotional support (Poortvliet, Anseel, & Theuwis, ). This reinforces the need for additional research examining the relationships between GO, interpersonal exchanges, and managers’ emotional exhaustion.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, empirical evidence has shown that performance goal orientation is unrelated to learning and performance in challenging situations (Chen & Mathieu, 2008;Payne, Youngcourt, & Beaubien, 2007). We thus keep in line with past advocates to examine exclusively how learning goal-oriented individuals navigate challenging organizational environments (Brophy, 2005;Huang & Luthans, 2014;Poortvliet, Anseel, & Theuwis, 2015), by extending its investigation into the newcomer socialization context.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 58%
“…Although, hypothesis H1b, and H1c held strong support from PLS-path modeling results, yet, despite enough literature support for significant role of administration leadership (ADML) in organizational performance (García-Morales et al, 2008;Bryman, 2007;Amey, 2006), the empirical results for H1a (β=-0.033, t=0.544, p=0.293) couldn't empirically support H1a to materialize the significant positive relationship between ADML and UP. The insignificant result regarding H1a is also in line with previous findings (Poortvliet et al, 2015;Menguc et al, 2013;Karatepe and Olugbade, 2009;Wu et al, 2013).…”
Section: Discussionsupporting
confidence: 91%